Endothelial specific prolyl hydroxylase domain-containing protein 2 deficiency attenuates aging-related obesity and exercise intolerance - Lihong Pan; Xiaochen He; Rui Xu; Umesh Bhattarai; Ziru Niu; Jussara do Carmo; Yuxiang Sun; Heng Zeng; John S. Clemmer; Jian-Xiong Chen; Yingjie Chen (GeroScience, 2024)
Obesity and exercise intolerance greatly reduce the life quality of older people. Prolyl hydroxylase domain-containing protein 2 (PHD2) is an important enzyme in modulating hypoxia-inducible factor-alpha (HIF) protein. Using vascular endothelial cell-specific PHD2 gene knockout (PHD2 ECKO) mice, we investigated the role of endothelial PHD2 in aging-related obesity and exercise capacity. Briefly, PHD2 ECKO mice were obtained by crossing PHD2-floxed mice with VE-Cadherin (Cdh5)-Cre transgenic mice. The effect of PHD2 ECKO on obesity and exercise capacity in PHD2 ECKO mice and control PHD2 f/f mice were determined in young mice (6 to 7 months) and aged mice (16–18 months). We found that aged PHD2 ECKO mice, but not young mice, exhibited a lean phenotype, characterized by lower fat mass, and its ratio to lean weight, body weight, or tibial length, while their food uptake was not reduced compared with controls. Moreover, as compared with aged control mice, aged PHD2 ECKO mice exhibited increased oxygen consumption at rest and during exercise, and the maximum rate of oxygen consumption (VO 2 max) during exercise. Furthermore, as compared with corresponding control mice, both young and aged PHD2 ECKO mice demonstrated improved glucose tolerance and lower insulin resistance. Together, these data demonstrate that inhibition of vascular endothelial PHD2 signaling significantly attenuates aging-related obesity, exercise intolerance, and glucose intolerance.